Determining Islamic banks’ reputation: Do Islamic CSR, zakat, non-halal fund, and Islamic corporate governance matter? - Wardiwiyono, Sartini; Hamdun, Nabil Ghazy; Pambudi, Dwi Santosa (Journal of Accounting and Investment, 2025)
Research aims: This study investigates the significance of Islamic Corporate Social Responsibility (ICSR), zakat, non-halal funds, and corporate governance in shaping the reputation of Islamic banks in Indonesia.Design/Methodology/Approach: It utilizes secondary data from various sources through documentation and content analysis methods. A sample of 106 observations was selected using purposive sampling from Islamic commercial banks registered by the Financial Services Authority from 2016 to 2023. Four research hypotheses were formulated and tested using multiple regression analysis.Research findings: The analysis results indicate that ICSR and zakat positively impact the reputation of Islamic commercial banks, whereas the involvement of non-halal funds may diminish their reputation. Insufficient evidence supported the fourth hypothesis, stating that Islamic corporate governance positively affects the reputation of Islamic banks.Theoretical contribution/Originality: This study advances Islamic and sustainable finance by employing eight years of data (2016 to 2023), surpassing prior works with older data and shorter coverage. It also applies a multidimensional approach that captures both positive drivers and reputational risks in Islamic banks. Furthermore, integrating multiple theoretical perspectives offers a novel triangulation, enhancing originality and enriching the scholarly discourse in this domain.Practitioner/Policy implication: The findings of this study provide current empirical insights that can assist Islamic banking practitioners in strengthening their institutions' credibility and public image by optimizing the positive drivers and managing reputational risks. Policymakers can utilize these findings to develop strategic initiatives to enhance Islamic banks' reputation, which may, in turn, contribute to expanding their market share.Research limitation/Implication: This study is limited by the reliance on Islamic corporate governance indicators that may not be sufficiently visible to stakeholders, constraining their observable impact on Islamic bank reputation. Future research should adopt measures such as governance disclosure quality, stakeholder awareness, or perception-based approaches such as surveys and content analysis to better capture how governance influences reputation.